Determinants of foreign direct investment in Malaysia / Nazatul Akmar Mohd Shah - Mohd Shah, Nazatul Akmar (Faculty of Business and Management, 2020)
The purpose of this study is to examine the determinants of foreign direct investment in Malaysia. The determinants are inflation rate (IR), gross domestic product (GDP), exchange rate (ER), trade openness (TRO) and Unemployment rate (UNPR). The study was using time series data from1988 to 2018 by using yearly data. Multiple linear regression test has been used in this study. The result shows that inflation rate and gross domestic product have positive and significant relationship towards foreign direct investment in Malaysia. Meanwhile, there is insignificant relationship between exchange rate, trade openness and unemployment rate on foreign direct investment in Malaysia. It means exchange rate, trade openness and unemployment rate has no significant effect on Foreign direct investment in Malaysia. Based on the result obtained, recommendation are made for the significant of study to help them in improving the foreign direct investment inflow in Malaysia for long run.